Hyponatremia Intervention Trial (HIT): Study Protocol of a Randomized, Controlled, Parallel-Group Trial With Blinded Outcome Assessment - Refardt, Julie; Pelouto, Anissa; Potasso, Laura; Hoorn, Ewout J.; Christ-Crain, Mirjam (Frontiers in Medicine, 2021)
Background – Hyponatremia is the most common electrolyte disorder with a prevalence of up to 30% in hospitalized patients. In contrast to acute hyponatremia where the need for immediate treatment is well recognized, chronic hyponatremia is often considered not clinically relevant. This is illustrated by reports showing that appropriate laboratory tests are ordered in <50% of patients and that up to 75% are still hyponatremic at discharge. At the same time, emerging evidence suggests an association between hyponatremia and adverse events including increased risk of mortality and rehospitalization. Methods – This is a randomized (1:1 ratio) controlled, superiority, parallel-group international multi-center trial with blinded outcome assessment. In total 2278 participants will be enrolled. Participants will be randomly assigned to undergo either targeted correction of plasma sodium levels or standard of care during hospitalization. The primary outcome is the combined risk of death or rehospitalization within 30 days. Discussion –All data on hyponatremia and mortality are derived from observational studies and often lack methodologic robustness. Consequently, the direct impact of hyponatremia on mortality and rehospitalization risk is still debated, resulting in a clinical equipoise whether in-hospital chronic hyponatremia should be treated or not. Therefore, a randomized controlled trial is required to study whether targeted plasma sodium correction reduces the risk of mortality and rehospitalization associated with hyponatremia. Clinical trial registration - clinicaltrials.gov. Registration number: NCT 03557957